2020
DOI: 10.3389/fphys.2020.617668
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Assessment of Hemodynamic, Metabolic and Ionic Consequences During Blood Flow Restriction Training

Abstract: Purpose: Medically recommended training often faces the dilemma that necessary mechanical intensities for muscle adaptations exceed patients' physical capacity. In this regard, blood flow restriction (BFR) training is becoming increasingly popular because it enables gains in muscle mass and strength despite using low-mechanical loads combined with external venous occlusion. Since the underlying mechanisms are still unknown, we applied invasive measurements during exercise with and without BFR to promote physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Blood-Flow-Restriction Exercises (BFRE) are a new training method that is characterized by the use of specialized tourniquets to restrict venous and reduce arterial blood flow during the exercise in the working limb to increase metabolic stress. Since BFRE can gain significant effects on muscle mass and strength by using only low mechanical loads ( Ferraz et al, 2018 ; Franz et al, 2020 ) its application in patients with degenerative joint diseases could be able to improve the applicability and effectiveness of prehabilitation concepts ( Franz et al, 2018 ; Žargi et al, 2018 ; Kacin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blood-Flow-Restriction Exercises (BFRE) are a new training method that is characterized by the use of specialized tourniquets to restrict venous and reduce arterial blood flow during the exercise in the working limb to increase metabolic stress. Since BFRE can gain significant effects on muscle mass and strength by using only low mechanical loads ( Ferraz et al, 2018 ; Franz et al, 2020 ) its application in patients with degenerative joint diseases could be able to improve the applicability and effectiveness of prehabilitation concepts ( Franz et al, 2018 ; Žargi et al, 2018 ; Kacin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other parts of the vascular system are similarly stressed during BFRT. A previous study demonstrated that BFRT in healthy subjects could acutely increase venous hypertension by ∼60 mmHg (Franz et al, 2020). While a healthy venous system can likely tolerate these increases with functioning venous valves in a longitudinal training program, patients with venous insufficiency or postoperative lymphedema might experience worsening of the cardiovascular health status induced by BFRT (Franz et al, 2020).…”
Section: Hypertension Blood Pressure Heart Rate Variability Angiogene...mentioning
confidence: 99%
“…By changing the body position from horizontal to vertical, blood flow through the legs increases from 8% to 23%. The establishment of new physical and hemodynamic conditions in the blood vessels of the legs are the main factors for the appearance of varicose veins [1][2][3].…”
Section: Introductionmentioning
confidence: 99%